2021
DOI: 10.3390/ani11072096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Kefir Source on Fermentation, Aerobic Stability, and Microbial Community of Alfalfa Silage

Abstract: The present study has been one of the first attempts to thoroughly examine the effects of different kefir sources on fermentation characteristics, aerobic stability, and microbial communities of alfalfa silages. The effects of commercial kefir (CK) and homemade kefir culture (HK) applied with untreated a common control (CON) and three different application doses (5.0, 5.7, and 6.0 log cfu g−1) on wilted alfalfa and stored at an ambient temperature of 25–30 °C are studied. After 45 days of ensiling, fermentatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The moisture level and chemical composition of the TMR were the other categories that contributed the most. These results are similar to those obtained by Koç et al [44], who reported that the moisture level, the type of ensiled plant, and its parts are more important than biological treatments for adequate forage conservation.…”
Section: Discussionsupporting
confidence: 91%
“…The moisture level and chemical composition of the TMR were the other categories that contributed the most. These results are similar to those obtained by Koç et al [44], who reported that the moisture level, the type of ensiled plant, and its parts are more important than biological treatments for adequate forage conservation.…”
Section: Discussionsupporting
confidence: 91%
“…The restraining activity of urea on spoilage microorganisms, including yeast and mold, was also stated by Fang et al [19]. Furthermore Koç et al [27] stated that such factors could affect the aerobic stability of silage, such as the initial epiphytic LAB population and its abundance, additive types, organic acid, and WSC content of ensiled material. These results mirror previous studies examining LB and urea on silages' aerobic stability.…”
Section: Effect Of Urea Treatment and L Buchneri Forms On Aerobic Sta...mentioning
confidence: 84%
“…The WSC (water-soluble carbohydrate) content of the silages was determined using a 0.2% anthrone reagent [25]. The pH, ammonia nitrogen (NH 3 -N), and organic acid content of the silage samples was determined after extracting a representative 20 g of fresh silage in 180 mL of distilled water at room temperature for 1 h. A digital pH meter (inoLab ph 730, WTW, Weilheim, Germany) and a microdistillation apparatus were deployed for the determination of pH and NH 3 -N analysis [27]. After deproteinization of the silage extract with a mixture of metaphosphoric acid and formic acid (3:1, v:v), the organic acid content of the silages, i.e., acetic acid (AA), propionic acid (PA), butyric acid (BA), was determined using a gas chromatograph (Shimadzu GC-201, Kyoto, Japan) with a capillary column (Restek, Bellefonte, PA, USA; 30 m, id: 0.25 mm, f.t.…”
Section: Chemical and Microbiological Analysesmentioning
confidence: 99%